The impact of an integrated electronic health record on nurse time at the bedside: A pre-post continuous time and motion study. Issue 1 (February 2020) - Walker, Rachel M.; Burmeister, Elizabeth; Jeffrey, Carol; Birgan, Sean; Garrahy, Elizabeth; Andrews, Jenny; Hada, Adriana; Aitken, Leanne M.
Abstract: Background: Evidence about the effectiveness of electronic health records in improving nursing workload efficiency is uncertain. Aim: To measure, compare and describe nurse time spent on patient care prior to, and following implementation of an integrated electronic health record roll-out using a standardised approach. Design: Structured, continuous observation, pre-post time and motion design. Methods: Continuous observations took place in general wards in surgical and medical divisions of a tertiary hospital in South East Queensland from November 2015 to July 2017. Trained nurse observers independently observed and recorded patient care provided by consenting direct-care nurses over the course of an entire clinical shift in surgical wards or during medication rounds in medical wards. Care activities were timed and coded into categories (direct care, indirect care, ward related activities, documentation, personal and miscellaneous activities), and additional elements that influence nursing care. Descriptive statistics including frequency, percentages and median duration were reported for care activities with differences between pre- and post-implementation reported. Findings: Direct-care nurses (n = 51) were observed for the duration of an entire clinical shift or during a medication round with a total of 6209 activities observed in both divisions. Most nursing activities occurred at the patient's bedside prior to and following the implementation of an integrated electronic health record. In the surgical division, direct care activities (such as assessing patient needs and preparing and administering ordered medications), and ward related activities (such as cleaning and clerical work) showed a significant decrease ( p  = <0.001), although both had significant increases in median duration. The number of indirect care activities (such as verbal reporting) also increased ( p  =  0.010), although there was a downward trend in their median duration ( p  =  0.015). Documentation (such as computer data entry) increased significantly in number of activities ( p  = <0.001), and median duration ( p  =  0.002). In the medical division, there were no significant changes in direct or indirect care or ward related activities or median time. However, documentation activities and associated median duration increased significantly ( p  = <0.001). Discussion: There was a significant increase in median time for documentation activities within an 18-month period following roll-out. However, this increase occurred as a result of the integrated electronic health record roll-out. Pre-implementation training assisted nurse adaptation. Workflows may improve as clinicians become more familiar with the digital system. Conclusion: While the move from paper-based patient records to an integrated electronic health record did not significantly change the amount of nurse time at the bedside, or for the preparation and administration of ordered medications, there was a clear and consistent trend of increased documentation time and activities following implementation of the electronic health record. This knowledge may assist nurse leaders when implementing electronic health records.